Original paper Prevalence of dermatophytes in interdigital spaces in HIV patients - Gniadek, Agnieszka; Skóra, Magdalena; Garlicki, Aleksander; Gądek, Aneta; B. Macura, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Introduction : Human immunodeficiency virus (HIV) infection and acquired immune deficiency syndrome (AIDS), both are related to higher prevalence of mycoses, especially oral candidosis, but also superficial mycoses. Fungal infections of the skin and its appendages are the most frequent dermatological complications in HIV patients and clinical manifestations of those infections are often atypical and more severe than in immunocompetent individuals. Aim: The purpose of the study was evaluation of the presence of dermatophytes in foot interdigital spaces in HIV patients in relation with various factors concerning the patient. Material and methods: The population under study were patients at the Infectious Diseases Clinic. The research comprised filling in questionnaires, physical examinations, evaluation of immunological status, and mycological examination of swabs from interdigital spaces. Results : Out of the 120 HIV infected patients under study, foot skin lesions were observed in 40 cases (33.3%) while dermatophytes were isolated from 12 patients (10%). Trichophyton mentagrophytes was isolated from 7 patients (5.8%), and Trichophyton rubrum from 6 (5.0%); both of the species were isolated from 1 patient. The prevalence of dermatophytes did not depend on the patient’s sex, sexual orientation, CD4 cells count, HCV co-infection, antiretroviral therapy nor clinical manifestations on the feet. Conclusions : The prevalence of dermatophytes in foot interdigital spaces in HIV patients amounted to 10% (similarly as in imunocompetent individuals) and did not depend significantly on any of the factors tested. It appears that contact with the fungi is the main factor responsible for infection.